Housing as a Process: Transformations of Incremental Houses in Informal Settlements - Rabbaniyah, Hafsah Intifadhoh; Almadina, Alif Faricha; Sarif, Naufal Kholid Masro (Universitas Muhammadiyah Surakarta, 2026)
Incremental housing emerges as one of the strategies adopted by communities in informal settlements. Incremental housing develops gradually over time, influenced by increasing household needs and adjusted to residents’ capacity to access adequate housing. This study examines incremental housing from a housing-as-a-process perspective within an informal settlement located in Sleman, Yogyakarta. A qualitative research approach is employed by analyzing physical transformations occurring in dwellings and examining the relationship between spatial aspects and economic capacity, which emerges as a key factor in informal settlements. Out of 36 buildings identified within the study area, five incremental housing units were selected as case studies. The analysis refers to the concept of housing as a process proposed by Turner and the theory of housing transformation articulated by Habraken. The findings indicate that the housing process is predominantly characterized by transformational forms in the form of horizontal and vertical additions, along with elimination in certain cases. The study also reveals the integration of economic activities within residential spaces. Overall, economic capacity is found to be the primary factor controlling the housing process in the cases examined.